Resistance in the Bluegrass : empowering the commonwealth - Alexander, Farrah (The University Press of Kentucky, 2022)
"From the anti-segregation sit-ins of the 1960s to the 2020 protests in response to the killing of Breonna Taylor, the rest of the nation-and often the world-has watched as Kentuckians boldly fought against injustice. In Resistance in the Bluegrass, Farrah Alexander outlines how Kentucky's activists have opposed racism, discrimination, economic inequality, and practices that accelerate climate change; advocated for better education, more humane immigration policies, and appropriate political representation; and supported LGBTQ and women's rights, while also celebrating decades of Kentucky contributions to social justice movements and the people behind them. Resistance in the Bluegrass gives engaged citizens-and those who aim to become more engaged-inspiration and guidance for how they too can make a difference across the commonwealth. With interviews and issue-by-issue action items, Alexander reminds her readers that everyday citizens who step up to make a difference are at the heart of all social change. Optimistic and accessible, Resistance in the Bluegrass is a people's history and guide that calls Kentuckians of all backgrounds to action"--